CINA DI UJUNG TIMUR JAWA - Retno Winarni; Bambang Samsu Badriyanto; Edy Burhan Arifin (Faculty of Humanities, Jember University, 2011)
The Chinese was considered the foreign people in Besuki Residency, despite of they hadsettled in Java northeast coast, even some had become administrators in the private land ofthe area. This article identifies and describes why they were able to be the administratorsin the area from the end of 18th to the beginning of 19th century. The problems to discuss are the relationship between Chinese administrators and the indigenous government and their relationship to the people. This study shows that there were differences and similaritiesbetween Chinese contract handlers (Chinese landlords) and Chinese as administrators.They were differentiated by the way of earning wide land and the way of getting power.The landlords had the right to manage wide land by renting or buying from the colonialgovernment. Meanwhile, Chinese administrators were promoted as the head of area becausetheir merit for colonial government. However, in managing the rented district both of them had similiar tendency; governing by feudal manner from which they considered themselvesthe owners of the land.